PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPERCAYAAN KONSUMEN DI HOME CREDIT AEON MALL BSD - Muhammad Abdul Rohim; Mutmainnah (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine whether there is an influence between service quality and brand image on consumer trust at Home Credit Aeon Mall BSD. both partially and simultaneously. The method used is descriptive associative method. In sampling, the Slovin formula was used and 99 respondents were obtained. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, coefficient of determination analysis and hypothesis testing. The results of this study are Service quality and brand image have a significant effect on consumer confidence with the regression equation Y = 6.445 + 0.161 X1 + 1.011 X2. The coefficient of determination is 60.3% while the remaining 39.7% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (72.945> 3.09). Thus Ho is rejected and H3 is accepted. This means that there is a simultaneous significant influence between service quality and brand image on consumer trust at Home Credit Aeon Mall BSD. Keywords: Service Quality, Brand Image, Consumer Trust